Ligand Versatility in Supercrystal Formation. (8th September 2017) - Reichhelm, Annett; Haubold, Danny; Eychmüller, Alexander
Abstract: Supercrystals (SCs) offer the opportunity to integrate nanoparticles into current technologies without losing their unique and designable properties. In the past two decades, much research has been conducted, allowing the synthesis of differently shaped nanoparticles of various materials. Employing those building units, several methods have been developed enabling the preparation of an increasing number of different superstructures. In this review, an overview is given of the large versatility of surfactant molecules used for SC preparation. While SCs with uncharged organic ligands are by far the largest group, the use of charged or uncommon ligands allows the preparation of unique SCs and superlattices. Additionally, the influence of the ligands on the self‐assembly and properties of the resulting SCs is highlighted. Abstract : Herein, the influence of the surfactant species on supercrystal formation is discussed with regard to superlattice and structural diversity. The variety of different ligands is categorized into three groups: uncharged long‐chain organics, charged organics, and unusual ligands. While the first category includes the mostly‐used ligands, uncommon surfactants enable the preparation of unique superstructures.